BIODIVERSITY OF TERMITES IN TELANGANA STATE, INDIA - KRANTHIKUMAR, P.; RAO, APKA NAGESWARA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Termites play a key role in tropical and subtropical forest ecosystems as decomposers of the largest part of dead organic matter, playing a significant role in soil formation. Termites are polymorphic, eusocial insects, living in large communities of several hundred to millions of individuals, composed of reproductive forms together with numerous apterous sterile soldiers and workers there are about 2933 species of termites in 282 genera, 9 families that have been described so far in the world. They have widely dispersed as well as some temperate regions. India has high diversity with 295 species, 52 genera, 6 families. In Telangana 16 Species, 7 genera and 2 families of termites are already reported. The study was conducted in 5 places in Telangana state to investigate the termite’s species diversity. Termites were sampled with a standard 100×2 straight belt transect at 5 different places in Telangana state. 11 Species were collected from different parts of the plants, on dead wood, litter, dead tree stumps and leaf litter, logs and living trees.